Cogito? Descartes and thinking the world - Almog, Joseph (Oxford : Oxford University Press, 2008)
Decartes' maxim 'Cogito, ergo sum' is perhaps the most famous philosophical expression ever coined. This volume looks at the first half of the proposition - cogito. Almog calls this the 'thinking man's paradox' - that there can be, in the natural world and as part and parcel of it, a creature that thinks.
Description based on print version record.
Includes bibliographical references and index.
Keywords: d; Thought and thinking